Prescripción de los delitos contra la indemnidad y libertad sexual de los menores de edad: problemas aplicativos del artículo 369 quater del Código penal - Cabezas Cabezas, Carlos (Política criminal, 2013)
Article 369 quater of the Chilean Penal Code created by Law 20.207 of 2007 amended the way the statute of limitations for crimes against sexual indemnity and liberty of minors is calculated. The following paper seeks to examine the exact juridical nature of said norm, that is, whether or not Article 369 quarter is in fact a circumstance that suspends the statute of limitations, as well as some problems that said norm can create when applied.